P2_5 Kinetic Impact Weapon Jabba - Lyons, Hannah; Carter, Samuel; Nixon, Josh; O'Sullivan, Rachael (Physics Special Topics, 2022)
Within the Star Wars fictional universe, the Death Star was a battle station used by a government called the Galactic Empire and was designed to be able to destroy planets with a “super laser”. For this paper, we considered a method to break apart the Death Star. Jabba the Hutt was a powerful gangster in the Star Wars universe and this paper looks into how the Death Star could have been broken apart by colliding a perfect sphere of multiple Jabba the Hutt characters with the Death Star. We found that the total number of Jabba the Hutt characters was 4.018x10^25.